Investigating the stability of perovskite light-emitting diodes - Warby, J (2020)
Metal halide perovskite semiconductors have recently attracted significant attention as a class of materials with huge potential for a wide array of optoelectronic applications. They have shown great promise as emitters in light-emitting diodes where they demonstrate emission wavelength tunability across the entire visible spectrum, narrow emission spectra and high EQEEL in excess of 20%. Despite this excellent performance they have poor operational stability, resulting in lifetimes of 250 hours in the best case.